Analysis of the Impact of Coffee Consumption on Adolescent Cardiovascular Performance: An Observational Study in the Adolescent Community in Jakarta, Indonesia - Muhammad Dzakwan Dwi Putra; Lontoh, Susy Olivia (HM Publisher, 2024)
Introduction: Coffee is a popular drink among adolescents. However, its effect on cardiovascular performance in this population remains unclear. This study aims to analyze the relationship between coffee consumption and cardiovascular performance in adolescents in Jakarta, Indonesia. Methods: Cross-sectional observational research was conducted on 350 adolescents aged 15-18 years in Jakarta. Coffee consumption data was collected through a structured questionnaire, while cardiovascular performance was assessed through measurements of blood pressure, heart rate and body mass index (BMI). Logistic regression analysis was used to identify the association between coffee consumption and cardiovascular performance, with adjustment for potential confounding factors. Results: The results of this study provide evidence that excessive coffee consumption (>2 cups/day) can increase blood pressure and resting heart rate in adolescents. However, moderate coffee consumption (1-2 cups/day) does not appear to have a significant negative impact on cardiovascular performance. Conclusion: Excessive coffee consumption (>2 cups/day) has a significant negative impact on adolescents' cardiovascular performance, namely increasing blood pressure and resting heart rate. However, further research is needed to understand the long-term effects and mechanisms underlying this relationship.